Averting a Global Environmental Collapse : the Role of Anthropology and Local Knowledge. - Reuter, Thomas (Cambridge Scholars Publishing, 2015)
The numerous and varied indicators of environmental risks point toward the likelihood of a systemic and catastrophic ecological failure at some point during this century. Political inaction and cultural resistance, meanwhile, are even preventing the implementation of already available technical solutions, which has led many experts to conclude that averting a global environmental catastrophe is, foremost, a socio-political, rather than a technical, challenge. The World Science Union (ICSU) has recognized that knowledge of the social sciences is indispensable for facilitating the major socio-cu.